Do rugby league players under-report concussion symptoms? A cross-sectional study of elite teams based in Australia. Issue 1 (19th January 2021) - Longworth, Thomas; McDonald, Andrew; Cunningham, Corey; Khan, Hussain; Fitzpatrick, Jane
Abstract : Objective: To determine the rate of under-reporting of concussion and its symptoms in elite rugby league players in Australia. Methods: The study was conducted in the preseason of the 2020 National Rugby League (NRL) competition. A total of 151 male, NRL club contracted rugby league players across three professional clubs participated. The participants completed a voluntary, anonymous survey exploring player demographics, concussion data, under-reporting instances and reasons for under-reporting over the 2018 and 2019 rugby league seasons. Results: 17.2% of surveyed players reported sustaining a likely concussion over the past 2 years and not reporting to medical staff. 22% of NRL first grade players admitted to not reporting at least one concussion during the 2018 and 2019 seasons. The most common reason not to report was the player 'not wanting to be ruled out of the game or training session' (57.7%), followed by 'not wanting to let down the coaches or teammates' (23.1%). 85.4% of surveyed players reported having concussion education by their club in the previous two seasons. Conclusions: 17.2 % of elite rugby league players in Australia chose not to report likely concussive episodes and concussion-related symptoms during the 2018 and 2019 seasons. Clinicians need to be aware of under-reporting in athletes when assessing players following head injuries. The findings highlight the need for development of validated, objective testing for concussion following sports-associated head injury.